Users and Search in Archival Databases (Atlanti, 2016)
Users searching for information in archival databases may rely only on themselves and on their experiences. They cannot rely on the help of archivist, as if they could if researching the traditional paper based finding aids. It is of course necessary to keep in mind that the search can be carried out only for data entered in the database. The first survey of users of archival information systems in Slovenia was presented in 2014. For the first time, in the archival profession in Slovenia and in the region, authors tried to introduce the basic concepts and theories in the field of user behaviour in information systems. The article presents the review of the literature relating to the user’s behaviour and reports on the results of the analyses of online accessible database SIRAnet. It presents partial results of a broader research conducted within the preparation of the doctoral thesis dealing with the creation of authority records within archival databases.
Keywords: use; users; information systems; archives; archival database; finding aids